BEST Trial - Coltrera, Francesca (MD Conference Express, 2015)
Percutaneous coronary intervention with second-generation everolimus-eluting stents was inferior to coronary artery bypass graft surgery in patients with multivessel coronary artery disease in the open-label prospective randomized BEST trial. The composite primary outcome (all-cause death, myocardial infarction, target vessel revascularization) occurred more frequently in patients randomized to percutaneous coronary intervention.